2011
DOI: 10.2527/jas.2010-3129
|View full text |Cite
|
Sign up to set email alerts
|

Minor beak trimming in chickens leads to loss of mechanoreception and magnetoreception1

Abstract: Routine removal of the tip of the beak of chickens within the poultry industry leads to changes in pecking behavior, which have previously been interpreted as being indicative of pain. By analyzing the force of pecks, with and without the topical application of an analgesic to the beak, we investigated if changes in pecking behavior were due to a loss of sensitivity in the beak or were pain related. Pecking behavior was compared between intact-beak and beak-trimmed chicks with or without topical application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 17 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…This may point to the single-domain receptors described in the nasal region (e.g., Beason and Nichols 1984, Beason and Brennan 1986; Williams and Wild 2001), but it appears highly unlikely that the externally applied anesthetic could have reached them. The observation that young chickens with the tip of their beak removed, as routinely done in the poultry industry, were impaired in locating a magnetic anomaly (Freire et al 2011) also suggests a position of the receptors further in front of the beak.…”
Section: Resultsmentioning
confidence: 99%
“…This may point to the single-domain receptors described in the nasal region (e.g., Beason and Nichols 1984, Beason and Brennan 1986; Williams and Wild 2001), but it appears highly unlikely that the externally applied anesthetic could have reached them. The observation that young chickens with the tip of their beak removed, as routinely done in the poultry industry, were impaired in locating a magnetic anomaly (Freire et al 2011) also suggests a position of the receptors further in front of the beak.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, beak trimming led to impaired function of the magnetoreceptors and mechanoreceptors of the beak (Freire et al, 2011). In a recent study, it was shown that hot-blade beak trimming at the day of hatching in layingstrain chicks did not result in pain (measured until 9 days of age).…”
Section: Beak Trimming or Partial Amputation Of The Beakmentioning
confidence: 99%
“…In a recent study, it was shown that hot-blade beak trimming at the day of hatching in layingstrain chicks did not result in pain (measured until 9 days of age). Instead, beak trimming led to impaired function of the magnetoreceptors and mechanoreceptors of the beak (Freire et al, 2011).…”
Section: Beak Trimming or Partial Amputation Of The Beakmentioning
confidence: 99%
“…Studies have given neurological evidence that the beak trimming procedure itself can cause both acute and chronic pain of hens. Furthermore, adverse impacts on the beak function and sensitivity limit the freedom of expression of normal behaviors [12] . A general ban on beak trimming already exists in European Union countries.…”
Section: Introduction mentioning
confidence: 99%